Distribution of Coral Reef and Seagrass Ecosystems’s Inorganic Carbon in the Waters of Beras Basah Bontang, East Kalimantan - Irwan Ramadhan Ritonga; S. Supriharyono; Boedi Hendrarto (International Journal of Science and Engineering, 2013)
Inorganic carbon is closely related to the calcification process (CaCO3), which is the main constituent of coral reefs or microorganisms that exist in the oceans such as foraminifera and cocolitoporit. Inorganic carbon is also closely linked to the chemical processes that occur when carbon dioxide gas (CO2) dissolved in water. The research of inorganic carbon in the waters of Beras Basah was carried out in January, February and March 2012. The purpose of this study was to understand the distribution and concentration of total inorganic carbon (CT) in coral reef and seagrass ecosystems as well as the correlation of Beras Basah. The results showed that the concentration of total inorganic carbon (CT) in January average 1166.503 μmol/kgSW, February average 1115.599 μmol/kgSW, and then in March the average 987.443 μmol/kgSW. Distribution patterns of total inorganic carbon (CT) is vectoral, where in January, the concentration of total inorganic carbon (CT) was highest in the Southeast region, was in February in the South and Southeast, while in March shifted to North region of Beras Basah Island. The concentration difference is thought to be influenced by pH and the seasons, tides, biochemical processes, and biological activity. Doi: 10.12777/ijse.5.1.1-5 [How to cite this article: Ritonga, I.R., Supriharyono, and Henderarto, B. (2013). Distribution of Coral Reef and Seagrass Ecosystems’s Inorganic Carbon in the Waters of Beras Basah Bontang, East Kalimantan. International Journal of Science and Engineering, 5(1),1-6. Doi: 10.12777/ijse.5.1.1-5]